Protection of Disability in the World of Work Through Law Number 8 of 2016 - Nurhayati, Sherly Putri; Badriyah, Firyal Nurul; Firdaningrum, Ayunda; Maulida, Nabila Amalia; Mumtazah, Eny Faizah; Harmako, Vira Giatyffany; Pamungkas, Ayu Ajeng (Disable, 2025)
Persons with disabilities in Indonesia continue to face numerous obstacles in accessing decent employment, despite the enactment of legal protections such as Law Number 8 of 2016, which is intended to safeguard their rights. Although this regulation is intended to serve as a strong foundation for promoting equality in the labor market, its implementation has not yet met expectations. Findings from this study indicate that the policy's implementation remains suboptimal due to weak institutional oversight, limited employer awareness of the capabilities of persons with disabilities, inadequate workplace accessibility, insufficient dissemination of disability rights, lack of incentives for inclusive employers, and the scarcity of necessary support facilities. These issues were identified through legislative, conceptual, and comparative approaches involving both primary legal materials and relevant secondary sources. To foster equal employment opportunities, strategic measures are needed, such as strengthening labor supervision systems, offering fiscal incentives to inclusive companies, improving the physical accessibility of work environments, and providing comprehensive job training programs tailored for persons with disabilities